(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes and analyzes samples of the cultural heritage of Uzbekistan stored in museums of the Russian Federation. Discussions are given about the history of samples of the cultural heritage of Uzbekistan coming to Russia and the current state of their preservation. An overview of large museums in Russia is provided, which store samples of material and spiritual culture, and the history of their study.